(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2025)
The study investigated effect of teacher professional qualifications on learners’ reading achievement in multilingual learning contexts of Livingstone District. The study used a quantitative approach and adopted and experimental design on three grade 1 teachers who were holding different qualifications in the same school and district. The study variables included phonemic awareness, phonics, fluency, vocabulary and comprehension. The study found that learners taught by the teacher with a Bachelor’s in Primary Education and a Primary Teacher’s Diploma achieved the highest post test scores (Cohen’s d = 1.33), followed by those instructed by the teacher with a Primary Teacher’s Diploma only (Cohen’s d = 0.85) while the lowest performance was recorded by the class taught by the teacher with a Bachelor’s Degree in English Language and History (Cohen’s d = 0.84). These results suggest that specialised training in primary education, particularly at the bachelor’s level, provides teachers with more superior pedagogical competences necessary for effective literacy instruction in multilingual learning contexts. The study recommended that primary schools should strengthen Continuing Professional Development (CPD) through tailored initiatives. These initiatives could include classroom demonstrations, collaborative workshops, and mentorship opportunities, all aimed at improving teachers’ instructional strategies.